Systems biomarkers for papillary thyroid cancer prognosis and treatment through multi-omics networks - TURANLI, BESTE; ARĞA, KAZIM YALÇIN; ÖZBEK SARICA, PEMRA (ELSEVIER SCIENCE INC, 2022)
The identification of biomolecules associated with papillary thyroid cancer (PTC) has upmost importance for the elucidation of the disease mechanism and the development of effective diagnostic and treatment strategies. Despite particular findings in this regard, a holistic analysis encompassing molecular data from different bio-logical levels has been lacking. In the present study, a meta-analysis of four transcriptome datasets was per -formed to identify gene expression signatures in PTC, and reporter molecules were determined by mapping gene expression data onto three major cellular networks, i.e., transcriptional regulatory, protein-protein interaction, and metabolic networks. We identified 282 common genes that were differentially expressed in all PTC datasets. In addition, six proteins (FYN, JUN, LYN, PML, SIN3A, and RARA), two Erb-B2 receptors (ERBB2 and ERBB4), two cyclin-dependent receptors (CDK1 and CDK2), and three histone deacetylase receptors (HDAC1, HDAC2, and HDAC3) came into prominence as proteomic signatures in addition to several metabolites including lactaldehyde and proline at the metabolome level. Significant associations with calcium and MAPK signaling pathways and transcriptional and post-transcriptional activities of 12 TFs and 110 miRNAs were also observed at the regulatory level. Among them, six miRNAs (miR-30b-3p, miR-15b-5p, let-7a-5p, miR-130b-3p, miR-424-5p, and miR-193b-3p) were associated with PTC for the first time in the literature, and the expression levels of miR-30b-3p, miR-15b-5p, and let-7a-5p were found to be predictive of disease prognosis. Drug repositioning and molecular docking simulations revealed that 5 drugs (prochlorperazine, meclizine, rottlerin, cephaeline, and tretinoin) may be useful in the treatment of PTC. Consequently, we report here biomolecule candidates that may be considered as prognostic biomarkers or potential therapeutic targets for further experimental and clinical trials for PTC.
Keywords: Papillary thyroid carcinoma; Thyroid cancer; Biomarker; Regulatory network; Protein-protein interaction network; Metabolic network; TYROSINE KINASE INHIBITORS; FOCAL ADHESION KINASE; EXPRESSION PROFILES; GENE-EXPRESSION; MOLECULAR SIGNATURES; CELL PROLIFERATION; HSP90 INHIBITION; DOWN-REGULATION; RETINOIC ACID; UP-REGULATION